2017
DOI: 10.13005/ojc/330639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modified Clay on the Morphological and Thermal Properties of PLA/PBAT Nanocomposites.

Abstract: In this study, new biodegradable polylactic acid/poly butylene adipate-co-terephthalate nanocomposites were developed and prepared using the melt blending method. Sodium montmorillonite clay was modified using organic surfactant, octadecyl ammonium bromide, novel dimethyl dioctadecyl ammonium bromide. A commercial organomodified montmorillonite, Cloisite 20A was also used as comparison. Increased interlayer spacing, reduced free water molecule within montmorillonite clay gallery spacing and existence of alkyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
2
Order By: Relevance
“…Osman and co‐workers observed that adding 1% Cloisite® 20A increased the T onset in PBAT/PLA blends, 84 but this behavior was not seen in this work with the nanocomposite membranes. However, the authors did not obtain a porous membrane, which is the case of this project.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…Osman and co‐workers observed that adding 1% Cloisite® 20A increased the T onset in PBAT/PLA blends, 84 but this behavior was not seen in this work with the nanocomposite membranes. However, the authors did not obtain a porous membrane, which is the case of this project.…”
Section: Resultscontrasting
confidence: 60%
“…Niazi and co-workers showed that adding cellulose in PVA increased the crystallinity, relative humidity, and tensile strength limit of the membranes. 83 Osman and co-workers observed that adding 1% Cloisite ® 20A increased the T onset in PBAT/PLA blends, 84 but this behavior was not seen in this work with the nanocomposite membranes. However, the authors did not obtain a porous membrane, which is the case of this project.…”
Section: Thermogravimetric Analysis (Tga)contrasting
confidence: 62%
“…The structure observations are confirmed by the impact tests results, where the impact resistance for PLA-PBAT materials was higher than for pure PLA. However, for other studies where plastic deformation mechanism was revealed, the impact resistance was improved several time [89]. The appearance of the composite structure presented in the Figure 10 is dominated by the presence of the flax fibers.…”
Section: Composite Structure-scanning Electron Microscopy Analysismentioning
confidence: 78%
“…This helps to improve the compatibility between PLA and PBAT. Other authors [ 23 ] introduced modified clay into PLA/PBAT to improve the properties of the blends. Hydrogen bonding was suspected from interactions between hydroxyl groups from clay interlayer galleries and PLA/PBAT blends.…”
Section: Introductionmentioning
confidence: 99%